A finite-time fuzzy adaptive output-feedback fault-tolerant control for underactuated wheeled mobile robots systems - Pingfan Liu; Shaocheng Tong (Journal of Automation and Intelligence)
This paper investigates the adaptive fuzzy finite-time output-feedback fault-tolerant control (FTC) problem for a class of nonlinear underactuated wheeled mobile robots (UWMRs) system with intermittent actuator faults. The UWMR system includes unknown nonlinear dynamics and immeasurable states. Fuzzy logic systems (FLSs) are utilized to work out immeasurable functions. Furthermore, with the support of the backstepping control technique and adaptive fuzzy state observer, a fuzzy adaptive finite-time output-feedback FTC scheme is developed under the intermittent actuator faults. It is testifying the scheme can ensure the controlled nonlinear UWMRs is stable and the estimation errors are convergent. Finally, the comparison results and simulation validate the effectiveness of the proposed fuzzy adaptive finite-time FTC approach.